2013
DOI: 10.1007/s13762-013-0350-9
|View full text |Cite
|
Sign up to set email alerts
|

Heavy metals concentration in soils under rainfed agro-ecosystems and their relationship with soil properties and management practices

Abstract: Heavy metals are governed by parent material of soils and influenced by the soil physicochemical properties and soil and crop management practices. This paper evaluates total heavy metal concentrations in rainfed soils under diverse management practices of tropical India. Vertisols (clayey soils with high shrink/swell capacity) had the highest concentrations of heavy metals. However, chromium (Cr) content was above the threshold value in Aridisol [calcium carbonate (CaCO 3 )]-containing soils of the arid envir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 38 publications
1
19
0
Order By: Relevance
“…Previous research identified significant positive correlations of TOC with metals (Gao & Chen, ; Dou et al ., ). Organic carbon is one of the main sources of nutrients in the topsoil; thus, it was expected that these correlations would be positive (Srinivasarao et al ., ; Gellaw et al ., ), confirming the affinity of the studied extractable metals for organic compounds (Esmaeili et al ., ). In relation to pH, our results were different from several studies, where a negative relationship between exchangeable heavy metals and pH is normally reported (Pereira et al ., ; Perez‐Esteban et al ., ; Czarnecki & Düring, ; Wu et al ., ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research identified significant positive correlations of TOC with metals (Gao & Chen, ; Dou et al ., ). Organic carbon is one of the main sources of nutrients in the topsoil; thus, it was expected that these correlations would be positive (Srinivasarao et al ., ; Gellaw et al ., ), confirming the affinity of the studied extractable metals for organic compounds (Esmaeili et al ., ). In relation to pH, our results were different from several studies, where a negative relationship between exchangeable heavy metals and pH is normally reported (Pereira et al ., ; Perez‐Esteban et al ., ; Czarnecki & Düring, ; Wu et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…In our work, the concentration of heavy metals was lower than the thresholds recommended by the European Union with the exception of Cd, which had some sampling points with a value higher than 3 (Table ). Nevertheless, the values observed are much lower than those observed in some other agricultural (Wu et al ., ; Farrag et al ., ; Esmaeili et al ., ; Srinivasarao et al ., ) and industrial (Krishna & Govil, ; Massas et al ., 13) areas. Reforestation of the agricultural area, the low clay content of the soils, and the closing of the TV factory may have contributed to these low values.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Composite addition to the soil increased the adsorption sites that resulted in more amount of metals in the solid phase leading to a higher adsorption intensity than that of the untreated soil. Among the metals studied, Cu maintained a higher adsorption intensity due to higher affinity for adsorption sites than that of Zn, Cd and Ni in the treated and untreated soils (Shaheen et al 2013;Srinivasarao et al 2014;Shaheen et al 2015a &b;Kang et al 2016). Desorption rate can be used to characterize the degree of metal binding to the adsorbent.…”
Section: Distribution Coefficientsmentioning
confidence: 96%
“…The typically dark colour of vertisols results from clay-organic complexes, whilst Fe-titanium (Ti)-Mn oxides also contribute to the pigmentation [27]. Most vertisols are inherently fertile and studies in India [28,29] and elsewhere [30] have demonstrated that the high clay content exerts dominant control over essential pools of Fe, Mn, Zn, Cu, Co and Ni and their [29,31], whereas soil pH (c. 7-8) and higher CaCO 3 contents result in lower concentrations of Fe, Mn and Zn [30,31]. In view of the high smectite content of the vertisols, it is surprising that the study area is among the most metaldeficient regions in Central India, indicating that only a small fraction of metals is bioavailable [31].…”
Section: Chemical and Mineralogical Characteristics Of Vertisols And mentioning
confidence: 99%